From Serfdom to Socialism - Hardie, James Keir, 1856-1915 (Book collections on Project MUSE., 2016)
'The first man from the midst of the working class who completely understood them, completely championed them ... never deserted them, never turned his back on a single principle which he had professed, never drifted away from his class in thought, in feeling or in faith.' John Bruce Glasier 'France had her Jaures, Germany her Bebel and Liebknecht, Austria her Victor Adler, Russia her Lenin. Britain produced, and continues to produce, men to carry on the struggle of the poor, but no one who more personifies the spirit of that struggle than the miner from the coalfields of Lanarkshire.' James Maxton Keir Hardie was the founder of the Labour Party, a pioneer trade unionist, a tireless campaigner for women's rights, and the first working man ever to be elected to Parliament. As a key text for the first generation of Labour Party activists, From Serfdom to Socialism stands both as a founding document of the Labour Party and as the fullest exposition of Hardie's political thought. It draws together into a coherent and explicitly socialist whole Hardie's - often disparate - ideas on history, religion, women's rights, and local and national government. In signalling the arrival of the Labour Party on the national stage, and defining all that it stood for, this book was to change the political landscape of Britain forever.